Accelerated long-term forgetting: A sensitive paradigm for detecting subtle cognitive impairment and evaluating BACE1 inhibitor efficacy in preclinical Alzheimer's disease - Ohno, Masuo (Frontiers in Dementia, 2023)
Given a long preclinical stage of Alzheimer’s disease (AD) continuum before the onset of dementia, there is a growing demand for tools capable of detecting the earliest feature of subtle cognitive impairment and optimizing recruitment to clinical trials for potentially disease-modifying therapeutic interventions such as BACE1 inhibitors. Now that all BACE1 inhibitor programs in symptomatic and prodromal AD populations have ended in failure, trials need to shift to target the earlier preclinical stage. However, evaluating cognitive efficacy (if any) in asymptomatic AD individuals is a great challenge. In this context, accelerated long-term forgetting (ALF) is emerging as a sensitive cognitive measure that can discriminate between presymptomatic individuals with high risks for developing AD and healthy controls. ALF is characterized by increased forgetting rates over extended delays (e.g., days, weeks, months) despite normal learning and short-term retention on standard memory assessments that typically use around 30-min delays. This review provides an overview of recent progress in animal model and clinical studies on this topic, focusing on the utility and underlying mechanism of ALF that may be applicable to earlier diagnosis and BACE1 inhibitor efficacy evaluation at a preclinical stage of AD.